HeartMate 3: new challenges in ventricular tachycardia ablation. Issue 4 (17th November 2021) - Nof, Eyal; Peichl, Petr; Stojadinovic, Predrag; Arceluz, Martin; Maury, Philippe; Katz, Moshe; Tedrow, Usha B; Singh, Robin M; Narui, Ryohsuke; John, Roy M; Stevenson, William G; Beinart, Roy; et al.
Abstract: Aim: To describe clinical characteristics, procedural details, specific challenges, and outcomes in patients with HeartMate3™ (HM3), a left ventricular assist device system with a magnetically levitated pump, undergoing ventricular tachycardia ablation (VTA). Methods and results: Data were collected from patients with an HM3 system who underwent VTA in seven tertiary centres. Data included baseline patient characteristics, procedural data, mortality, and arrhythmia-free survival. The study cohort included 19 patients with cardiomyopathy presenting with ventricular tachycardia (VT) (53% with VT storm). Ventricular tachycardias were induced in 89% of patients and a total of 41 VTs were observed. Severe electromagnetic interference was present on the surface electrocardiogram. Hence, VT localization required analysis of intra-cardiac signals or the use of filter in the 40–20 Hz range. The large house pump HM3 design obscured the cannula inflow and therefore multi imaging modalities were necessary to avoid catheter entrapment in the cannula. A total of 32 VTs were mapped and were successfully ablated (31% to the anterior wall, 38% to the septum and only 9% to the inflow cannula region). Non-inducibility of any VT was reached in 11 patients (58%). Over a follow-up of 429 (interquartile range 101–692) days, 5 (26%) patients underwent a redo VT ablation due to recurrent VTA and 2 (11%) patients died. Conclusions: Ventricular tachycardia ablation in patients with HM3 is feasible and safe when done in the appropriate setup. Long-term arrhythmia-free survival is acceptable but not well predicted by non-inducibility at the end of the procedure.